2020
DOI: 10.1111/imb.12638
|View full text |Cite|
|
Sign up to set email alerts
|

Mating‐based regulation and ligand binding of an odorant‐binding protein support the inverse sexual communication of the greater wax moth, Galleria mellonella (Lepidoptera: Pyralidae)

Abstract: In moths, sex pheromones play a key role in mate finding. These chemicals are transported in the antennae by odorant-binding proteins (OBPs). Commonly, males encounter conspecific females; therefore, several OBPs are male-biased. Less is known, however, about how the olfactory system of moths has evolved toward inverse sexual communication, ie where females seek males. Therefore, the objective of this study was to identify the profile of OBPs and their expression patterns in the bee hive pest, Galleria mellone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…More recently, Zhao et al (2019) performed transcriptome sequencing on G. mellonella antennae and identified several chemosensory genes (e.g., 46 ORs, 25 IRs, 22 OBPs, 20 CSPs and 2 SNMPs). Similarly, Lizana et al (2020) also identified 20 OBP genes from this moth species. However, the number of OBPs in G. mellonella is relatively lesser compared to other Pyralid moths, such as C. suppressalis, Ostrinia furnacalis, and Cnaphalocrocis medinalis, with 23, 26 and 26 OBP genes, respectively (Liu et al, 2017;Zhang et al, 2015b;Cao et al, 2014).…”
Section: Introductionmentioning
confidence: 77%
“…More recently, Zhao et al (2019) performed transcriptome sequencing on G. mellonella antennae and identified several chemosensory genes (e.g., 46 ORs, 25 IRs, 22 OBPs, 20 CSPs and 2 SNMPs). Similarly, Lizana et al (2020) also identified 20 OBP genes from this moth species. However, the number of OBPs in G. mellonella is relatively lesser compared to other Pyralid moths, such as C. suppressalis, Ostrinia furnacalis, and Cnaphalocrocis medinalis, with 23, 26 and 26 OBP genes, respectively (Liu et al, 2017;Zhang et al, 2015b;Cao et al, 2014).…”
Section: Introductionmentioning
confidence: 77%
“…The greater wax moth, G. mellonella , is a global beehive pest that has remained without either effective or environmentally friendly control methods. Recent advances have focused on the olfactory system of G. mellonella adults to understand its chemical ecology ( Zhao et al, 2019 ; Lizana et al, 2020 ). However, less focus has been given to larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…An antennal transcriptome reported by Zhao et al (2019) and retrieved from Bioproject PRJNA616199 (SRA study SRP254512) as well as larval transcriptome from 454 Sequencing data within the Bioproject PRJEB2452 (SRA study ERP000555) were used. Finally, an assembled adult head transcriptome from our laboratory and reported in Lizana et al (2020) was used. Homology searches were performed using a manually built amino acid database in FASTA format for GSTs from moths, such as B. mori , Helicoverpa assulta, and Amyelois transitella .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article by Lizana et al . (2020), a duplicated image was detected post‐publication. During the preparation of the article Fig.…”
Section: Figurementioning
confidence: 99%